2017
DOI: 10.1177/2156587217692491
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Oxidative Stress and Inflammation by Portulaca oleracea in Streptozotocin-Induced Diabetic Rats

Abstract: The present study was designed to investigate the protective effect of the aqueous extract of Portulaca oleracea against hyperglycemic, oxidative damage and inflammation in the serum of streptozotocin (STZ)-induced diabetic rats. In the present study, the rats were divided into the following groups of 8 animals each: control, untreated diabetic, 3 Portulaca oleracea (100, 200, 400 mg/kg/d)–treated diabetic groups. At the end of the 4-week period, glucose, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…The current study found that the M. communis fruits hydroalcoholic extract have hypolipidemic property in diabetic rats which may be very crucial in preventing or treating of diabetes complications particularly atherosclerotic heart diseases. Hyperlipidemic and hyperglycemic activities which demonstrated in the current investigation may be associated with the oxidative stress which generated MDA, induced lipid peroxidation and caused cells injuries [44][45][46].…”
Section: Discussionmentioning
confidence: 59%
“…The current study found that the M. communis fruits hydroalcoholic extract have hypolipidemic property in diabetic rats which may be very crucial in preventing or treating of diabetes complications particularly atherosclerotic heart diseases. Hyperlipidemic and hyperglycemic activities which demonstrated in the current investigation may be associated with the oxidative stress which generated MDA, induced lipid peroxidation and caused cells injuries [44][45][46].…”
Section: Discussionmentioning
confidence: 59%
“…Administration of the aqueous extract of P. oleracea (400 mg/kg/d) to the STZ-induced rats, recovered decreased TAS and GSH as well as increased MDA; IL-6 and TNF-α level 35 . The protective effect of P. oleracea against diabetes in mice was studied.…”
Section: Pharmacological Activitiesmentioning
confidence: 91%
“…STZ with the help of low-affinity glucose protein-2 transporter enters the pancreatic β-cells and thus results into selective damage to insulin-producing islet β cells. In STZ treated rats both local and systemic oxidative stress is the cause of damage to pancreas and the progress of diabetes 35 .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…In rats fed high-fat diets, it was seen that purslane decreased TG, TC, and LDL levels [32] and similarly it decreased TC and TG levels in hypercholesterolemic rats [33]. In rats with DM induced by streptozotocin, it was shown that purslane had hypoglycemic [34] and antioxidant effects [35].…”
Section: Leaf Vegetablesmentioning
confidence: 99%